Correlation between the built environment and sociology: A critical review of residential segregation and social housing policy in Iran - Armita Khalatbari LIMAKI (Smart Cities and Regional Development Journal)
This paper critically reviews the correlation between the built environment and sociology as it pertains to residential segregation and social housing policy in Iran. The objective is to identify design strategies that minimize the risk of social isolation, promote social interaction, and foster a sense of community within affordable housing zones. The literature review includes existing research on urban segregation and social sustainability, with a focus on architectural solutions. Case studies are utilized to exemplify both positive and negative social outcomes related to urban segregation and identify effective design elements. The findings highlight the complex nature of residential segregation and its impact on social isolation, social capital, and social exclusion. The built environment contributes to the problem by facilitating the creation of isolated communities, and architects have a crucial role in addressing them. The results suggest that a comprehensive social housing policy is necessary to improve the quality of social housing and reduce residential segregation in Iran. Finally, the paper provides practical design strategies to promote social interaction, enhance accessibility and mobility, create mixed-use developments, and incorporate sustainable design features in social housing policy. By using design strategies that support social sustainability and inclusiveness, architects can create thriving and sustainable urban environments that prioritize the needs of marginalized communities.